Innovative modeling framework for combined sewer overflows prediction. Issue 1 (2nd January 2017) - Morales, Viviana M.; Mier, Jose M.; Garcia, Marcelo H.
Abstract : Combined sewer overflows (CSOs) and street flooding are undesirable consequences of insufficient capacity of sewer networks and wastewater systems. These conditions degrade the water quality of the receiving waters, potentially damage infrastructure, and threaten public health. Significant efforts to prevent CSOs and alleviate flooding have been undertaken in Chicago, with the construction of the tunnel and reservoir plan (TARP). This study analyses the hydraulic response of the first tunnel built in Chicago "The Lawrence Avenue Tunnel" through a framework of hydrological and hydraulic models. This framework proved effective in CSO's volume, frequency and duration predictions as it yields simulation results of existing conditions that match well with available records. The findings also provide insights into the importance of system operation on CSOs occurrence and magnitude. Adaptive management of the tunnel during storm events is recommended to minimize the impact of CSOs.